Web-Based Population Data Management Application: Case Study: RW17 Citaliktik Soreang Office, Bandung District - Tedi Supriadi; Haris Supriatna; Miranti Adhita Scantya; Adjat Sudrajat; Ahfi Fauka Paranata (Informatics Management, Engineering and Information System Journal, 2023)
The RW17 Citaliktik Soreang office is one of the Residents' Associations, having its address at Kp. Citaliktik Soreang Islamic Boarding School has various kinds of resident activities. Currently, the population data collection at the Citaliktik RW17 Office is to collect citizen data conventionally according to its category. With this, it is necessary to implement an information system, the Population Data Collection Application, which is implemented through the website. The system will be developed using object-oriented software development and programming (OOAD) methods using a computer or laptop device. To assist the RW17 Citaliktik Soreang Office in improving the existing system with the hope that the processing and presentation of population data, which is still conventional, can make it easier to make this population data collection application. The result of making the application is a Population Data Collection Application at the RW17 Citaliktik Soreang Office.